City of the beasts - Allende, Isabel (USA : Harper Collins Publishers, 2002)
When the fifteen year old Alexander Cold accompanies his individualistic grandmother on an expedition to find a beast in the Amazon, he experience ancient wonders and supernatural world as he tries to avert disaster for Indians
Keywords: Amazon River Valley -- Fiction; Supernatural -- Fiction; Adventure and adventures -- Fiction; Grandmothers -- Fiction